A copper-aluminum composite foil, a method for manufacturing the same, and an application thereof
Patent Information
- Application Number
- CN202610776627.9
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2026-06-01
- Publication Date
- 2026-09-01
AI Technical Summary
[0007]本发明的目的在于提供一种铜铝复合箔及其制备方法和应用,以解决现有技术中纯铜方案成本高且重量大、纯铝方案焊接性差,以及现有复合方案界面结合不可靠的技术问题
1)本发明通过设计金属增厚铜层保证了优异的导电、导热和可焊性,解决了铝表面难焊和易氧化的问题;中间的高纯铝芯基层则起到了轻量化和降低成本的核心作用,使得材料成本和重量显著降低;通过设计溅射晶种活化层、应力缓释过渡合金层,使铜铝复合箔的整体热膨胀系数介于铜和铝之间,与铝基底或FPC基材的热匹配性更优,显著降低了层间热应力,提升了长期可靠性;
Smart Images

Figure CN122669348A_ABST
Abstract
Description
Technical Field
[0001] This invention belongs to the technical fields of electronic conductive materials, CCS integrated busbars for power batteries, and metal-based printed circuit boards, specifically relating to a copper-aluminum composite foil, its preparation method, and its application. Background Technology
[0002] As new energy vehicles and electronic devices develop towards lightweight and highly integrated designs, higher requirements are being placed on copper foil, the core material for conductive connections and heat dissipation substrates, in terms of cost reduction, weight reduction, and reliability.
[0003] In existing technologies, CCS (Cells Contact System) integrated busbars generally use pure copper foil or copper busbars as conductive acquisition components. However, the high price and density of copper result in high module weight and cost. Furthermore, this hinders the integrated construction of flexible printed circuits (FPCs).
[0004] Similarly, in the field of aluminum substrates, pure copper foil is widely used as the circuit layer. However, pure copper is expensive and its coefficient of thermal expansion does not match that of the aluminum substrate. In the long-term hot and cold cycles, it is prone to interlayer delamination and solder joint fatigue failure.
[0005] To address these issues, the industry has attempted to directly replace copper foil with pure aluminum foil. However, aluminum surfaces are prone to oxidation, forming a non-conductive oxide film, resulting in poor weldability, high contact resistance, and insufficient voltage resistance and reliability to meet the stringent requirements of CCS and aluminum substrates for conductivity, weldability, and insulation. Existing copper-aluminum composite solutions generally suffer from common problems such as weak interfacial bonding strength, easy delamination, and high resistivity.
[0006] Therefore, there is an urgent need for a new type of conductive foil that combines the excellent conductivity and solderability of copper with the lightweight and low-cost advantages of aluminum, while also having a strong interface bond and high reliability. Summary of the Invention
[0007] The purpose of this invention is to provide a copper-aluminum composite foil, its preparation method, and its application, in order to solve the technical problems of high cost and heavy weight of pure copper solutions, poor weldability of pure aluminum solutions, and unreliable interfacial bonding of existing composite solutions.
[0008] To achieve the above objectives and technical effects, the technical solution adopted by this invention is as follows: A copper-aluminum composite foil, comprising: High-purity aluminum core base layer; A stress-relieving transition alloy layer is disposed on at least one side of the high-purity aluminum core base layer; A sputtered seed activation layer is set on the side of the stress relief transition alloy layer away from the high-purity aluminum core base layer; A thickened copper metal layer is disposed on the side of the sputtered seed activation layer away from the stress-relieving transition alloy layer; An insulating, anti-oxidation, and passivation protective layer is set on the side of the metal-thickened copper layer away from the sputtered seed activation layer; Each layer has an atomic-level metallurgical bonding interface, with no brittle phases, no continuous oxide layer, and no pores / cracks. It has high interlayer peel strength and good bonding stability.
[0009] Furthermore, the copper-aluminum composite foil is a single-sided five-layer composite structure, with the layers arranged from the outside to the inside as follows: an insulating anti-oxidation passivation protective layer, a metal thickened copper layer, a sputtered seed activation layer, a stress-relieving transition alloy layer, and a high-purity aluminum core base layer.
[0010] Furthermore, the copper-aluminum composite foil is a double-sided symmetrical seven-layer composite structure. Its layer structure is centered on a high-purity aluminum core base layer, with a stress-relieving transition alloy layer, a sputtered seed activation layer, and a metal thickening copper layer symmetrically arranged on both sides. An insulating anti-oxidation passivation protective layer is provided on the surface of the outermost metal thickening copper layer. The stress-relieving transition alloy layer and the sputtered seed activation layer are integrally formed by sputtering.
[0011] Furthermore, the total thickness of the copper-aluminum composite foil is between 12 and 100 μm.
[0012] Furthermore, the resistivity of the copper-aluminum composite foil is ≤1.9μΩ·cm, and the peel strength is ≥8N / cm.
[0013] Furthermore, the thickened copper layer is a pure copper layer formed on the sputtered seed activation layer by an electrochemical deposition process or a chemical plating process, and the thickness of the thickened copper layer is 50 nm to 5 μm.
[0014] Furthermore, the insulating and anti-oxidation passivation protective layer is a benzotriazole passivation layer or a silane chromium-free passivation layer, with a thickness of 10-200 nm.
[0015] This invention also discloses a method for preparing copper-aluminum composite foil, comprising the following steps: High-purity aluminum foil is provided as the base material and pretreated to obtain a high-purity aluminum core base layer; A composite structure is prepared on at least one side of a high-purity aluminum core substrate using an oxygen-free semi-molten rolling composite process or a vacuum plating composite process. The vacuum coating composite process includes: Sputtering integral molding steps: On the surface of the pretreated high-purity aluminum core base layer, a stress-relieving transition alloy layer and a sputtered seed activation layer are sequentially sputtered to form an atomic-level metallurgical bond; Thickening step: A thickened copper layer is formed on the sputtered seed activation layer by electrochemical deposition or chemical plating process; Post-processing steps: After thickening, vacuum temperature-controlled heat treatment is performed to precisely control the temperature and pressure and maintain an oxygen-free composite atmosphere, effectively suppressing the precipitation of copper-aluminum eutectic brittle phase and strengthening the metallurgical bonding of atomic interdiffusion at the multilayer interface; finally, a nanoscale insulating, anti-oxidation, and passivation protective layer is prepared on the outermost layer.
[0016] Furthermore, the electrochemical deposition process uses an acidic copper sulfate electrolyte system, controlling the electrolyte temperature at 25–45°C and the current density at 1–5 A / dm³. 2 The electroplating time is 5–30 min, and the pH value of the system is 1.0–2.5.
[0017] Furthermore, the electroless plating process employs a potassium sodium tartrate complex copper system, controlling the plating bath temperature at 40–65°C, the electroless plating time at 10–45 min, and the plating bath pH at 11.5–13.0.
[0018] The present invention also discloses the application of copper-aluminum composite foil in CCS integrated busbar, wherein the copper-aluminum composite foil replaces pure copper foil and is used to manufacture the acquisition lines and / or busbars of the CCS integrated busbar of power battery.
[0019] Furthermore, the copper-aluminum composite foil is integrated with other components of the CCS integrated busbar through FPC bonding, welding, and die-cutting processes.
[0020] The present invention also discloses the application of copper-aluminum composite foil in aluminum substrate, wherein the copper-aluminum composite foil replaces pure copper foil and is used as a conductive layer for circuits, and is bonded to the aluminum substrate by a lamination process.
[0021] Compared with the prior art, the beneficial effects of the present invention are as follows: 1) This invention ensures excellent electrical conductivity, thermal conductivity and solderability by designing a thickened copper layer, solving the problems of difficult soldering and easy oxidation of aluminum surfaces; the high-purity aluminum core in the middle plays a key role in weight reduction and cost reduction, resulting in a significant reduction in material cost and weight; by designing a sputtered seed activation layer and a stress-relieving transition alloy layer, the overall thermal expansion coefficient of the copper-aluminum composite foil is between that of copper and aluminum, resulting in better thermal matching with aluminum substrates or FPC substrates, significantly reducing interlayer thermal stress and improving long-term reliability; 2) Excellent electrical and thermal conductivity: The volume conductivity is over 90% of that of pure copper, there is no high-resistivity layer at the interface, and the current carrying and heat dissipation performance matches industry standards. 3) Strong interface bonding: metallurgical bonding, no delamination, no blistering, and resistant to high and low temperature cycles and mechanical stress; 4) Significantly reduced costs: Material costs are 30-50% lower than pure copper foil, greatly reducing copper consumption; 5) Lightweight performance: The density is about 40% of that of pure copper, resulting in a weight reduction of ≥30%, thus improving the lightweight level of PCBs; 6) The product can be directly adapted to existing standard production lines such as etching, die-cutting, pressing, and electroplating, and downstream customers do not need to make large-scale equipment modifications. Attached Figure Description
[0022] Figure 1 This is a schematic diagram of the structure of Example 1; Figure 2 This is a schematic diagram of the structure of Example 2. Detailed Implementation
[0023] The present invention will now be described in detail so that its advantages and features can be more easily understood by those skilled in the art, thereby providing a clearer and more explicit definition of the scope of protection of the present invention.
[0024] The following provides a brief overview of one or more aspects to offer a basic understanding of them. This overview is not an exhaustive summary of all conceived aspects, nor is it intended to identify key or decisive elements of all aspects, nor to define the scope of any or all aspects. Its sole purpose is to present some concepts of one or more aspects in a simplified form to prepare for the more detailed descriptions that follow.
[0025] like Figure 1-2 As shown, this invention discloses a copper-aluminum composite foil, comprising: High-purity aluminum core base layer 1; A stress-relieving transition alloy layer 2 is disposed on at least one side of the high-purity aluminum core base layer 1; A sputtered seed activation layer 3 is set on the side of the stress relief transition alloy layer 2 that is away from the high-purity aluminum core base layer 1; A thickened copper layer 4 is disposed on the side of the sputtered seed activation layer 3 away from the stress relief transition alloy layer 2; An insulating, anti-oxidation, and passivation protective layer 5 is disposed on the side of the metal thickened copper layer 4 away from the sputtered seed activation layer 3; Each layer has an atomic-level metallurgical bonding interface.
[0026] In some embodiments, the copper-aluminum composite foil is a single-sided five-layer composite structure, and its layer structure from the outside to the inside is as follows: an insulating anti-oxidation passivation protective layer 5, a metal thickened copper layer 4, a sputtered seed activation layer 3, a stress-relieving transition alloy layer 2, and a high-purity aluminum core base layer 1.
[0027] In some other embodiments, the copper-aluminum composite foil is a double-sided symmetrical seven-layer composite structure. Its layer structure is centered on a high-purity aluminum core base layer 1, with a stress-relieving transition alloy layer 2, a sputtered seed activation layer 3, and a metal thickening copper layer 4 symmetrically arranged on both sides. An insulating anti-oxidation passivation protective layer 5 is provided on the surface of the outermost metal thickening copper layer 4. The stress-relieving transition alloy layer 2 and the sputtered seed activation layer 3 are integrally formed by sputtering and are regarded as one layer.
[0028] In some specific implementations, the total thickness of the copper-aluminum composite foil is between 12 and 100 μm.
[0029] In some specific implementations, the resistivity of the copper-aluminum composite foil is ≤1.9μΩ·cm, and the peel strength is ≥8N / cm.
[0030] In some specific embodiments, the thickened copper layer 4 is a pure copper layer formed on the sputtered seed activation layer by electrochemical deposition or chemical plating process, and the thickness of the thickened copper layer 4 is 50nm to 5μm.
[0031] In some specific embodiments, the insulating and anti-oxidation passivation protective layer 5 is a benzotriazole passivation layer or a silane chromium-free passivation layer with a thickness of 10-200 nm.
[0032] The benzotriazole passivation layer is obtained by impregnation and passivation treatment with benzotriazole solution at a temperature of 25-55℃, an impregnation time of 20s-3min, a pH value of 2.0-6.0, followed by rinsing with pure water and drying with hot air at 60-80℃.
[0033] The silane chromium-free passivation layer is obtained by treating with 0.5-3% silane at a temperature of 25-45℃, an impregnation time of 1-5 min, a curing temperature of 120-180℃, and a holding time of 15-40 min.
[0034] This invention also discloses a method for preparing copper-aluminum composite foil, comprising the following steps: High-purity aluminum foil is provided as the base material and pretreated to obtain a high-purity aluminum core base layer 1; A composite structure is prepared on at least one side of a high-purity aluminum core substrate 1 using an oxygen-free semi-molten rolling composite process or a vacuum plating composite process. The vacuum coating composite process includes: Sputtering integral molding steps: On the surface of the pretreated high-purity aluminum core base layer 1, a stress-relieving transition alloy layer 2 and a sputtered seed activation layer 3 are sequentially sputtered to form an atomic-level metallurgical bond. Thickening step: On the sputtered seed activation layer 3, a metal thickening copper layer 4 is formed by electrochemical deposition or chemical plating process; Post-processing steps: After thickening, vacuum temperature-controlled heat treatment is performed to precisely control the temperature and pressure and maintain an oxygen-free composite atmosphere, effectively inhibiting the precipitation of copper-aluminum eutectic brittle phase and strengthening the metallurgical bonding of atomic interdiffusion at the multi-layer interface; finally, a nano-scale insulating and anti-oxidation passivation protective layer 5 is prepared on the outermost layer to improve the material's resistance to damp heat, oxidation, and insulation and withstand voltage.
[0035] In some embodiments, the electrochemical deposition process uses an acidic copper sulfate electrolyte, controlling the electrolyte temperature at 25–45°C and the current density at 1–5 A / dm³. 2 The electroplating time is 5–30 min, and the system pH value is 1.0–2.5. The electrochemical deposition process precisely thickens the surface pure copper layer, resulting in a dense grain, high surface smoothness, and conductivity close to that of pure copper. This significantly reduces the cost and preparation time of the entire vacuum thick copper plating process.
[0036] In some embodiments, the electroless plating process employs a potassium sodium tartrate complex copper system, controlling the plating bath temperature at 40–65°C, the electroless plating time at 10–45 min, and the plating bath pH at 11.5–13.0. Pure copper is uniformly deposited via a self-catalytic reaction in the seed layer, requiring no external electric field. This results in low plating stress and good thickness uniformity, making it suitable for the fabrication of ultra-thin precision copper layers.
[0037] This invention also discloses the application of copper-aluminum composite foil in CCS integrated busbars, whereby the copper-aluminum composite foil replaces pure copper foil and is used to fabricate the acquisition lines and / or busbars of the CCS integrated busbars for power batteries.
[0038] The present invention also discloses the application of copper-aluminum composite foil in aluminum substrate, wherein the copper-aluminum composite foil replaces pure copper foil and is used as a conductive layer for circuits.
[0039] Example 1
[0040] like Figure 1 As shown, a copper-aluminum composite foil with a total thickness of 35μm has a double-sided symmetrical seven-layer composite structure. Its layer structure is centered on a high-purity aluminum core base layer 1, with a stress-relieving transition alloy layer 2, a sputtered seed activation layer 3, and a metal thickening copper layer 4 symmetrically arranged on both sides. An insulating anti-oxidation passivation protective layer 5 is arranged on the surface of the outermost metal thickening copper layer 4. Each layer is an atomic-level metallurgical bonding interface.
[0041] The thickness of the high-purity aluminum core base layer 1 is 25μm.
[0042] The stress-relieving transition alloy layer 2 and the sputtered seed activation layer 3 are integrally formed by sputtering and are considered as one layer.
[0043] The thickened copper layer 4 is a pure copper layer formed on the sputtered seed activation layer by an electrochemical deposition process. The thickness of the thickened copper layer is 4 μm.
[0044] The insulating and anti-oxidation passivation protective layer 5 is a benzotriazole passivation layer with a thickness of 10nm.
[0045] A method for preparing copper-aluminum composite foil includes the following steps: High-purity aluminum foil is provided as the base material, and it is subjected to degreasing, deoxidation and plasma activation pretreatment to obtain high-purity aluminum core base layer 1; A composite structure is prepared on a high-purity aluminum core substrate 1 using a vacuum plating composite process. The composite structure includes: a stress-relieving transition alloy layer 2, a sputtered seed activation layer 3, a metal thickening copper layer 4, and an insulating, anti-oxidation, and passivation protective layer 5. The vacuum coating composite process includes: Sputtering integral molding steps: After the pretreatment is completed, the high-purity aluminum core base layer 1 is sent into the vacuum sputtering chamber. On the surface of the pretreated high-purity aluminum core base layer 1, nickel-chromium is first deposited to form a stress relief transition alloy layer 2 through magnetron sputtering integral molding process. Then, copper is sputtered to form a sputtered seed activation layer 3, forming an atomic-level metallurgical bond. Thickening step: After sputtering is completed, the high-purity aluminum core base layer 1 is transferred into an oxygen-free closed electroplating tank, and a metal thickening copper layer 4 is formed on the sputtered seed activation layer 3 by electrochemical deposition process. Post-processing steps: After thickening, vacuum temperature-controlled heat treatment is performed to precisely control the temperature and pressure and maintain an oxygen-free composite atmosphere, effectively inhibiting the precipitation of copper-aluminum eutectic brittle phase and strengthening the metallurgical bonding of atomic interdiffusion at the multi-layer interface; finally, benzotriazole solution is used for impregnation passivation treatment (treatment temperature is 25℃, impregnation time is 1min, pH value is 2.0, pure water rinsing, and 60℃ hot air drying) to form a nano-level insulating and anti-oxidation passivation protective layer, improving the material's resistance to damp heat, oxidation, and insulation withstand voltage. After drying, it is wound up.
[0046] The electrochemical deposition process uses an acidic copper sulfate electrolyte system, with the electrolyte temperature controlled at 25℃ and the current density at 1A / dm³. 2 The electroplating time is 5 minutes, and the system pH value is 1.0. By using an electrochemical deposition process to precisely thicken the surface pure copper layer, the coating has dense grains, high surface smoothness, and conductivity close to that of pure copper, which can significantly reduce the cost and preparation time of the entire process of vacuum thick copper plating.
[0047] Example 2
[0048] like Figure 2 As shown, a copper-aluminum composite foil has a total thickness of 50μm and is a single-sided five-layer composite structure. The layers, from the outside to the inside, are: an insulating anti-oxidation passivation protective layer 5, a metal thickening copper layer 4, a sputtered seed activation layer 3, a stress-relieving transition alloy layer 2, and a high-purity aluminum core base layer 1.
[0049] The thickened copper layer 4 is a pure copper layer formed on the sputtered seed activation layer 3 by a chemical plating process, and the thickness of the thickened copper layer is 5μm.
[0050] The insulating and anti-oxidation passivation protective layer 5 is a benzotriazole passivation layer with a thickness of 200nm.
[0051] A method for preparing copper-aluminum composite foil includes the following steps: High-purity aluminum foil is provided as the base material and pretreated to obtain a high-purity aluminum core base layer 1; A composite structure was prepared on a high-purity aluminum core substrate 1 using a vacuum coating composite process; The vacuum coating composite process includes: Sputtering integral molding steps: On the surface of the pretreated high-purity aluminum core base layer 1, a stress-relieving transition alloy layer 2 and a sputtered seed activation layer 3 are sequentially sputtered to form an atomic-level metallurgical bond. Thickening step: On the sputtered seed activation layer 3, a metal thickening copper layer 4 is formed by electrochemical deposition or chemical plating process; Post-processing steps: After thickening, vacuum temperature-controlled heat treatment is performed to precisely control the temperature and pressure and maintain an oxygen-free composite atmosphere, effectively inhibiting the precipitation of copper-aluminum eutectic brittle phase and strengthening the metallurgical bonding of atomic interdiffusion at the multi-layer interface; finally, a nano-scale insulating and anti-oxidation passivation protective layer 5 is prepared on the outermost layer to improve the material's resistance to damp heat, oxidation, and insulation and withstand voltage.
[0052] The electroless plating process uses a potassium sodium tartrate complex copper system, controlling the plating bath temperature at 40℃, the electroless plating time at 10 min, and the pH value of the plating bath at 11.5. Pure copper is uniformly deposited by relying on the autocatalytic reaction of the seed layer, without the need for an external electric field. The plating layer has low stress and good thickness uniformity, making it suitable for the preparation of ultra-thin precision copper layers.
[0053] The rest is the same as in Example 1.
[0054] The copper-aluminum composite foil in Example 1 has a resistivity of only 1.9 μΩ·cm and an interlayer peel strength as high as 10 N / cm. After 1000 cycles under extreme temperature conditions ranging from -40℃ to 125℃, no delamination or blistering occurred. When applied to the acquisition circuit of the CCS-FPC in a power battery, it directly replaced the 35μm pure copper foil. Results showed that material costs were reduced by approximately 40%, copper consumption was significantly reduced, module weight was reduced by approximately 35%, welding resistance remained stable below 50 μΩ, insulation withstand voltage performance fully met the requirements of GB / T18384.3 standard, and long-term operational reliability was verified.
[0055] The copper-aluminum composite foil in Example 2 has a thermal conductivity of 210 W / (m·K), exhibits excellent etching performance, and achieves a yield of up to 99%. Replacing 50μm pure copper foil with it for the circuit layer of LED / power supply aluminum substrates reduces material costs by approximately 35%. In reliability testing, due to its overall thermal expansion coefficient being more compatible with the aluminum substrate, no issues of delamination between the circuit layer and the substrate or pad detachment were found after long-term high-temperature aging and thermal shock tests, resulting in a significantly extended service life.
[0056] Any parts or structures not specifically described in this invention can be made using existing technologies or products, and will not be elaborated upon here.
[0057] The above description is merely an embodiment of the present invention and does not limit the patent scope of the present invention. Any equivalent structural or procedural transformations made based on the content of the present invention specification, or direct or indirect applications in other related technical fields, are similarly included within the patent protection scope of the present invention.
Claims
1. A copper-aluminum composite foil, characterized in that, include: High-purity aluminum core base layer; A stress-relieving transition alloy layer is disposed on at least one side of the high-purity aluminum core base layer; A sputtered seed activation layer is set on the side of the stress relief transition alloy layer away from the high-purity aluminum core base layer; A thickened copper metal layer is disposed on the side of the sputtered seed activation layer away from the stress-relieving transition alloy layer; An insulating, anti-oxidation, and passivation protective layer is set on the side of the metal-thickened copper layer away from the sputtered seed activation layer.
2. The copper-aluminum composite foil according to claim 1, characterized in that, The copper-aluminum composite foil has a single-sided five-layer composite structure, and its layer structure from the outside to the inside is as follows: an insulating anti-oxidation passivation protective layer, a metal thickened copper layer, a sputtered seed activation layer, a stress-relieving transition alloy layer, and a high-purity aluminum core base layer.
3. The copper-aluminum composite foil according to claim 1, characterized in that, The copper-aluminum composite foil is a seven-layer composite structure with double-sided symmetry. Its layer structure is centered on a high-purity aluminum core base layer, with a stress-relieving transition alloy layer, a sputtered seed activation layer, and a metal thickening copper layer arranged symmetrically on both sides. An insulating, anti-oxidation, and passivation protective layer is set on the surface of the outermost metal thickening copper layer. The stress-relieving transition alloy layer and the sputtered seed activation layer are integrally formed by sputtering.
4. The copper-aluminum composite foil according to claim 1, characterized in that, The thickened copper layer is a pure copper layer formed on the sputtered seed activation layer by electrochemical deposition or chemical plating, and the thickness of the thickened copper layer is 50 nm to 5 μm.
5. The copper-aluminum composite foil according to claim 1, characterized in that, The insulating, anti-oxidation, and passivation protective layer is a benzotriazole passivation layer or a silane chromium-free passivation layer, with a thickness of 10–200 nm.
6. A method for preparing a copper-aluminum composite foil according to any one of claims 1-5, characterized in that, Includes the following steps: High-purity aluminum foil is provided as the base material and pretreated to obtain a high-purity aluminum core base layer; A composite structure is prepared on at least one side of a high-purity aluminum core substrate using an oxygen-free semi-molten rolling composite process or a vacuum plating composite process. The vacuum coating composite process includes: Sputtering integral molding steps: On the surface of the pretreated high-purity aluminum core base layer, a stress-relieving transition alloy layer and a sputtered seed activation layer are sequentially sputtered to form an atomic-level metallurgical bond; Thickening step: A thickened copper layer is formed on the sputtered seed activation layer by electrochemical deposition or chemical plating process; Post-processing steps: After thickening, vacuum temperature-controlled heat treatment is performed to precisely control the temperature and pressure and maintain an oxygen-free composite atmosphere, effectively suppressing the precipitation of copper-aluminum eutectic brittle phase and strengthening the metallurgical bonding of atomic interdiffusion at the multilayer interface; finally, a nanoscale insulating, anti-oxidation, and passivation protective layer is prepared on the outermost layer.
7. The method for preparing a copper-aluminum composite foil according to claim 6, characterized in that, The electrochemical deposition process uses an acidic copper sulfate electrolyte system, with the electrolyte temperature controlled at 25–45°C and the current density at 1–5 A / dm³. 2 The electroplating time is 5–30 min, and the pH value of the system is 1.0–2.
5.
8. The method for preparing a copper-aluminum composite foil according to claim 6, characterized in that, The electroless plating process uses a potassium sodium tartrate complex copper system, and controls the plating bath temperature to be 40-65℃, the electroless plating time to be 10-45 min, and the pH value of the plating bath to be 11.5-13.
0.
9. The application of the copper-aluminum composite foil according to any one of claims 1-5 in CCS integrated busbar, characterized in that, The copper-aluminum composite foil replaces pure copper foil and is used to fabricate the acquisition lines and / or busbars of the CCS integrated busbar for power batteries.
10. The application of the copper-aluminum composite foil according to any one of claims 1-5 in an aluminum substrate, characterized in that, The copper-aluminum composite foil replaces pure copper foil and is used as the conductive layer of the circuit.